Error Correction and Feedback in Speaking : A Comparative Study of Teacher (Lecturer) and Student Preferences in Responding Students’ Errors in Speaking at English Education Study Program - Bambang Irfani (Bandar Lampung University (UBL), 2014)
While it is strongly believed that students’ errors must be handled properly, it is crucial to note that teachers and students may have different perspectives upon the effective strategies to deal with the students’ errors, particularly in oral production. Hence, this research is focused on comparing the teacher and student preferences for error correction and feedback in speaking activities.This is a kind of survey research, where data were collected from all lecturers of Speaking subject – there were four – and all students taking the subjects of Speaking for General Purposes and Speaking for Academic Purposes presented in the first and third semester repectively. Data which were primarily collected through questionnaire were, then, analyzed qualitatively and quantitatively.Based on the analysis, it was revealed that there is a discrepancy among teachers and students in terms of beliefs about the relative importance of speaking features and preferences for error correction techniques in speaking activities.